Implementation of Character Education Through Audio Media Papuan Folk Stories in PKN Subjects at INPRES 36 Elementary School, Sorong Regency - Hajirah, Hajirah; Immawati, Sri; Firman, Firman (Universitas Muhammadiyah Makassar, 2025)
In the current era of globalization, along with the progress and development of the times and increasingly developing. This research aims to see how effective the implementation of character education through Papuan folklore audio media is in increasing students' understanding of good character values, as well as how much influence it has on students' attitudes and behavior at Elementary School of Inpres 36, Sorong Regency. This research uses a descriptive method with a qualitative approach, to explore an in-depth understanding of how character education is implemented through audio media of Papuan folk tales for elementary school students. The analytical descriptive method is a research method to explain the description of situations or events, phenomena that are occurring and are related to current conditions. Based on the research results, the use of audio media with Papuan folklore has proven to be effective in increasing students' understanding of character values. Based on the research results, the use of audio media with Papuan folklore has proven to be effective in increasing students' understanding of character values. Students show a positive response to the use of audio media in learning, and existing obstacles can be overcome well. The application of audio media in PKN learning helps students understand and apply character values such as courage, discipline, honesty, cooperation, responsibility, mutual cooperation, respect and love of culture. Teachers have a very important role in communicating the values contained in folklore with the real lives of students. Several challenges faced in The application of this method is due to limited facilities in schools due to the lack of electricity or internet connection in Malabam village in the morning so that the audio media used is only simple audio which is limited in use due to the battery power in the audio.